Cross-Cultural Adaptation Process of Japanese Expatriates in Indonesia - Windy Melliani Mandari; Rino Febrianno Boer (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Cross-cultural adaptation process is an ongoing issue for expatriates while working abroad, including Japanese expatriates working in Indonesian companies. This research aims to know the critical point and adaptation process of Japanese expatriates. The research method used was ethnography. Primary data collection techniques were in-depth interviews and observations. This research also included secondary data. Findings revealed that the adaptation process had an important role as it could lead to a comfortable interaction and reduce miscommunication at work. Important factors in the adaptation process were language fluency, work culture adjustment, media uses, daily interaction with Indonesians, interaction among Japanese in Indonesia, and real assistance for expatriates. There were three stages that expatriates had to go through, i.e., preparation, active, and final stage. The critical points in the adaptation process were language skills and willingness to accept changes.